A new twisted differential line structure in global bus design - Jiang, Zhanyuan; Hu, Shiyan; Shi, Weiping (2007 44th ACM/IEEE Design Automation Conference, 2007)
Twisted differential line structure can effectively reduce crosstalk noise on global bus, which foresees a wide applicability. However, measured performance based on fabricated circuits is much worse than simulated performance based on the layout. It is suspected that the via resistance variation is the cause. In this paper, our extensive simulation confirm this. A new redundant via insertion technique is proposed to reduce via variation and signal distortion. In addition, a new buffer insertion technique is proposed to synchronize the transmitted signals, thus further improving the effectiveness of the twisted differential line. Experimental results demonstrate that the new approaches are highly effective. Under a realistic setup, a 6GHz signal can be transmitted with high fidelity using the new approaches. In contrast, only a 100MHz signal can be reliably transmitted using a single-end model with power/ground shielding. In addition, compared to conventional twisted differential line structure, our new techniques can reduce the magnitude of noise by 45%. Furthermore, compared to unbuffered twisted differential line structure, the maximum signal phase difference is reduced from 37ps to 7ps by the new buffer insertion technique.